Collaborative Training in Research Methodology: a case of Malaysia and Laos - Low, Wah Yun; Azman Firdaus, Aliyyah Nuha Faiqah; Hashim, Azirah; Keovilay, Bouasavanh Keovilay; Osay, Vong Deuan; Vongsouangtham, Bounthieng; Soulignavong, Latsanyphone (AEI Insights, 2021)
One important aspect of the ASEAN vision is that ASEAN countries strive for equitable economic development and therefore concerted efforts must be made to narrow the development gap between ASEAN countries. This is prioritised in the Initiative for ASEAN Integration which outlines several activities that are designed to assist CLMV countries achieve deeper regional integration while supporting national development priorities and inclusive development. While there has been improvement, there is still significant variance in development achievements. The gaps are wide not only in achievements in income but also in education and health outcomes. This case study provides a description of a Malaysian and Lao collaboration in English language and research methodology training and the challenges faced in doing social science research among Lao academics. The collaboration addresses the developmental divide through knowledge exchange, engagement and collaboration, and capacity building in development between the parties involved.